2022
DOI: 10.3390/cancers14194573
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Dietary Phenolic Compounds to Improve Chemosensitivity of Anticancer Drugs

Abstract: Despite the significant advances and mechanistic understanding of tumor processes, therapeutic agents against different types of cancer still have a high rate of recurrence associated with the development of resistance by tumor cells. This chemoresistance involves several mechanisms, including the programming of glucose metabolism, mitochondrial damage, and lysosome dysfunction. However, combining several anticancer agents can decrease resistance and increase therapeutic efficacy. Furthermore, this treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Other polyphenolic compounds such as feruloyl quinic acid and caffeoylquinic acid reported in Table S1 were also detected in the leaves. These phenolic acids which form part of chlorogenic acids are known to possess anticarcinogenic properties due to their antioxidant activities (Makhafola et al, 2016; Bouyahya et al, 2022). When evaluating the superclasses present in the flowers of the two cutivars, the Phenylpropanoids and polyketide superclass (comprised of polyphenolic compounds) was less dominant.…”
Section: Resultsmentioning
confidence: 99%
“…Other polyphenolic compounds such as feruloyl quinic acid and caffeoylquinic acid reported in Table S1 were also detected in the leaves. These phenolic acids which form part of chlorogenic acids are known to possess anticarcinogenic properties due to their antioxidant activities (Makhafola et al, 2016; Bouyahya et al, 2022). When evaluating the superclasses present in the flowers of the two cutivars, the Phenylpropanoids and polyketide superclass (comprised of polyphenolic compounds) was less dominant.…”
Section: Resultsmentioning
confidence: 99%
“…Other polyphenolic compounds such as feruloyl quinic acid and caffeoylquinic acid reported in Table S1 were also detected in the leaves. These phenolic acids which form part of chlorogenic acids are known to possess anticarcinogenic properties due to their antioxidant activities (Makhafola et al, 2016 ; Bouyahya et al, 2022 ). When evaluating the superclasses present in the flowers of the two cutivars, the Phenylpropanoids and polyketide superclass (comprised of polyphenolic compounds) was less dominant.…”
Section: Resultsmentioning
confidence: 99%
“…NPs are gaining popularity in cancer treatment because they have fewer side effects, are less costly, and are more easily accessible than popular medications. A lecture through a published research review by Bouyahya et al, [41] showed that phenolic compounds are great sources of naturally occurring anticancer agents, offering various therapeutic and preventive options for the treatment of numerous cancer types. These chemicals can be employed solely or in conjunction with currently available anticancer medicines.…”
Section: Discussionmentioning
confidence: 99%